Retinal Neurovascular Changes in Patients With Ischemic Stroke Investigated by Optical Coherence Tomography Angiography - Liang, Yingying; Liu, Baoyi; Xiao, Yu; Zeng, Xiaomin; Wu, Guanrong; Du, Zijing; Fang, Ying; Hu, Yijun; Yang, Xiaohong; Yu, Honghua (Frontiers in Aging Neuroscience, 2022)
Background: To investigate retinal neurovascular structural changes in patients with ischemic stroke (IS) using optical coherence tomography angiography (OCTA). Methods: The cross-sectional study was conducted in Guangdong Provincial People’s Hospital, China, consisting of 159 eyes from IS patients and 109 eyes from age-matched control subjects. Retinal microvascular parameters including the vessel density (VD) of the superficial capillary plexus (SCP), deep capillary plexus (DCP) and radial peripapillary capillary (RPC), and neural parameters such as ganglion cell complex thickness (GCCt) and retinal nerve fibre layer thickness (RNFLt) were measured by OCTA. Results: The VD of SCP and DCP in the macular area were significantly reduced in IS patients compared to the control group (all p<0.001). The VD of RPC at the optic disc was also significantly reduced in IS patients (all p<0.05). IS patients showed reduced GCCt and RNFLt and increased GLV and FLV compared with the controls (all p<0.05). Among patients with IS, the parafovea SCP VD was positively correlated with GCCt (r=0.346-0.408, all p<0.001) but not with DCP VD (all p> 0.1). In the optic disc region, the whole image RPC VD was positively correlated with mean RNFLt (r=0. 467-0.548, all p<0.001). Conclusions: Reduction of retinal VD, GCCt and RNFLt was observed in patients with IS. The parafovea SCP VD and RPC VD were positively correlated with GCCt and RNFLt, respectively.